Comprehensive institutional review for climate resilient agriculture - Rana, Abdul Wajid; Pakistan Agricultural Capacity Enhancement Program; International Food Policy Research Institute (International Food Policy Research Institute, 2019)
Pakistan is vulnerable to climate change impacts. Like many developing countries, it is also facing the challenge of dealing with governance of climate change and restructuring associated institutions. It is estimated that the future cost of climate impact would be around $6 billion to $14 billion annually over the next 40 years. Ministry of Climate Change is now focusing in creating necessary infrastructure and platforms for policy decisions and implementation.